KEBIJAKAN PENETAPAN KUOTA PRODUKSI BATUBARA: ANALISIS DAN PENERAPANNYA DI DINAS PERTAMBANGAN DAN ENERGI PROVINSI KALIMANTAN TIMUR - . Istiadi (Jurnal Paradigma (JP), 2017)
The results showed the implementation of policies quotas coal production in the Department of Mines and Energy of the Province of East Kalimantan consists of standards or criteria used to memetapkan production quotas yet, while policy objectives quite clearly set the appropriate legislation, human resources both number and competence enough either because the officials charged by the educational background of Engineering Geology and Mining Engineering is very relevant to the Determination Policy Production quotas, but has not been supported by means of support teknlogi based information causes delays sasaran.Komunikasi information access to group leaders on the staff is able to provide insight about the policy that should be done particularly in regard to the establishment of quotas coal production, but not evenly understood by the target group because of the lack of socialization., the disposition can provide an understanding of the policy by the implementor to implement a policy that has been set, but there is no consistency implementor and lack of supervision influencing the policy can not be implemented effectively.Keywords: implementation, policy, fixing quota, coal